Childhood and Adolescent nodular lymphocyte predominant Hodgkin lymphoma ‐ A review of clinical outcome based on the histological variants. (26th June 2015) - Shankar, Ananth G.; Kirkwood, Amy A.; Hall, Georgina W.; Hayward, Janis; O'Hare, Patricia; Ramsay, Alan D.
Summary Nodular lymphocyte predominant Hodgkin lymphoma (nLPHL) comprises approximately 10–12% of all childhood Hodgkin lymphoma. As the majority have low stage disease recent years have seen a de‐escalation of treatment intensity to avoid treatment‐related morbidity. This report evaluates treatment outcome in children with histopathological variants of nLPHL after therapy de‐escalation. Biopsies from 60 patients were reviewed and histology categorized as typical (n = 47; 78%) or variant nLPHL (n = 13; 22%). Furthermore, presence of immunoglobulin D (IgD) expression by the lymphocyte predominant (LP) cells was assessed in 41 patients. Treatment outcomes were compared according to treatment received and histopathology of nLPHL. Compared to typical nLPHL, children with variant nLPHL had higher stage disease at diagnosis (stage III: 3/13; 23% vs. 3/47; 6%, P = 0·11), lower complete response rates (6/13; 46% vs. 38/47; 81%, P = 0·029) and higher relapse rates (2/13; 15% vs. 2/47; 4%, P = 0·20). Additionally, IgD expression by LP cells was associated with poorer treatment response and was more commonly seen in patients with variant nLPHL. (11/13; 85% vs. 15/28; 54%, P = 0·08). Variant histology appears to be indicative of a poorer prognosis in patients with early stage disease, and may be an important factor to take into account when moving towards reduced intensity treatment for nLPHL.